APAatlas: decoding alternative polyadenylation across human tissues. Issue Volume 48:Issue D1(2020) (5th October 2019) - Hong, Wei; Ruan, Hang; Zhang, Zhao; Ye, Youqiong; Liu, Yaoming; Li, Shengli; Jing, Ying; Zhang, Huiwen; Diao, Lixia; Liang, Han; Han, Leng
Abstract: Alternative polyadenylation (APA) is an RNA-processing mechanism on the 3′ terminus that generates distinct isoforms of mRNAs and/or other RNA polymerase II transcripts with different 3′UTR lengths. Widespread APA affects post-transcriptional gene regulation in mRNA translation, stability, and localization, and exhibits strong tissue specificity. However, no existing database provides comprehensive information about APA events in a large number of human normal tissues. Using the RNA-seq data from the Genotype-Tissue Expression project, we systematically identified APA events from 9475 samples across 53 human tissues and examined their associations with multiple traits and gene expression across tissues. We further developed APAatlas, a user-friendly database (https://hanlab.uth.edu/apa/ ) for searching, browsing and downloading related information. APAatlas will help the biomedical research community elucidate the functions and mechanisms of APA events in human tissues.